Astrology in the Middle Ages - Carey, Hilary M. (History compass, 2010)
The article reviews the history of astrology in the middle ages including its classical inheritance, ascendancy under Byzantium and Islam, and development in the Latin west. Mediaeval astrology was a part of learned, scientific culture. However, the translation movement in the high middle ages brought challenges of integration to the Latin west, reflected in condemnations and anxieties about the orthodoxy and morality of astrological judgements. It was not until relatively late that astrology was practised on a large scale in mediaeval courts and it never achieved the same level of prominence as it did under Islam. The final section considers new work on the history of astrology, including astrology and medicine and astrology and the court. The article considers major figures, including Claudius Ptolemaeus (Ptolemy), Isidore of Seville (c. 600 ad), Māshā’allāh (Messahallah) (c. 735-815), Abū Ma’shar (Albumasar), Ahmad ibn Yūsuf (870-904), John of Seville (fl. 1135-1153), Alfonso X (El Sabio) of Castile (1221-1284), Albertus Magnus (1206-1280), and the fifteenth-century astrologer historian, Simon de Phares. It is argued that astrology was an integral part of the mediaeval world view and it is impossible to understand mediaeval culture without taking it into account.